Simultaneous embolization of the right portal and hepatic veins before intrahepatic cholangiocarcinoma resection - Américo Gusmão Amorim; Olival Cirilo Lucena da Fonseca Neto; Raimundo Hugo Matias Furtado; Laécio Leitão Batista; Ludmilla Rodrigues Oliveira Costa; Igor Montenegro Galvão (Einstein (São Paulo), 2024)
ABSTRACT Major liver resections require extensive margins. Occasionally, insufficient parenchyma is available after surgery to maintain liver function. In such cases, vascular embolization in the affected lobe is necessary to induce contralateral lobe hypertrophy. We present a case of embolization of the right portal and hepatic veins prior to intrahepatic cholangiocarcinoma resection. Embolization was performed because of insufficient residual parenchyma on imaging studies. The patient recovered well with no signs of liver failure, and remains in remission at 3 years postoperatively. Knowledge of the use of this technique in association with surgical resection can reduce postoperative complications and allow the removal of larger tumors than those previously considered borderline.